Values Development in an Elementary School Guidance Program - Murphy, H. Joseph; Wells, Gordon S. (Canadian Journal of Counselling and Psychotherapy, 2012)
Role-playing activities were employed by an elementary school counsellor in anattempt to influence moral development. While support was not found for the thesis that moral reasoning and social perspective-taking levels are influenced by role-playing, evidence in support of the age-related nature of these constructs and their parallel pattern of development was found. Further research would be enhanced by valid measurement devices.